Integration of Card Sort Method and Self-Reflection in Learning Pancasila Values in Senior High School - Efendi, Yulius Rustan; Atiqa, Dyah Ayu; Dewi, Natalia Aristina (Actual Insight, 2025)
The acquisition of Pancasila values among adolescents is increasingly challenged by low student participation and the predominant use of technology for non-educational purposes. These factors have contributed to a decline in students’ comprehension and internalization of Pancasila values in daily life. This study aimed to examine the effectiveness of integrating the Card Sort method with structured self-reflection activities to enhance the understanding of Pancasila values among tenth-grade students at State Senior High School 6 Malang. A Classroom Action Research design guided by the Kemmis and McTaggart spiral model was employed, conducted over two cycles with thirty-three participants. Data were systematically collected through pre-tests, post-tests, classroom observations, and student reflection journals. The results demonstrated a substantial improvement in students’ understanding of Pancasila values, reflected in higher post-test scores and active engagement during learning activities. Furthermore, self-reflection activities enhanced students’ awareness of their civic rights, responsibilities, and attitudes as Indonesian citizens. The integration of collaborative, interactive, and reflective instructional strategies proved effective in promoting both cognitive learning outcomes and the cultivation of positive character traits aligned with Pancasila principles. These findings highlight the importance of implementing integrated collaborative and reflective pedagogical approaches in Pancasila Education to foster meaningful student engagement, participation, and internalization of civic values, particularly in the digital era.